Fast Zinc determination using commercial screen-printed carbon electrodes modified with bismuth nanostructures via pulsed electrodeposition - A. Rubino; R.B. Queirós (Talanta Open)
Electroanalytical devices based on screen-printed electrodes (SPEs) present a portable and cost-effective alternative to traditional laboratory analytical methods for detecting metal ions. This study investigates the development and application of commercially available screen-printed carbon electrodes (SPCEs) modified with Bi nanostructures for the detection of Zn in water/wastewater samples. By the application of pulsed electrodeposition (PED), Bi nanostructures are effectively anchored to the carbon-based working electrode of the screen-printed device (Bi-nano/SPCEs). The performance of those modified electrodes in Zn sensing was assessed using differential pulse voltammetry (DPV) in “drop-on-a-chip” configuration. Evaluations conducted with both standard solutions and real wastewater samples reveal that the electroanalytical device based on Bi-nano modified SPCEs exhibit promising sensitivity (1.21 μA cm-2 μg/L-1; 0.018 μA cm-2 μM-1) and repeatability (RSD < 10 %) with LOD and LOQ of 4.86 and 12.21 μg/L Zn(II), respectively (i.e., 0.075 and 0.188 μM), contextually guaranteeing rapid analysis (≤ 60 s) and high versatility in real samples analysis.